Apathy symptoms increase the risk of dementia conversion: a case‐matching cohort study on patients with post‐stroke mild cognitive impairment in China. Issue 2 (4th January 2021) - Zhao, Jiayi; Jin, Xianglan; Chen, Baoxin; Fu, Chen; Ji, Shaozhen; Shen, Wei; Wei, Jingjing; Zheng, Hong; Zhang, Yunling
Abstract: Background: Apathy is a neuropsychiatric symptom frequently observed in patients with cognitive impairment. It has been found to be a predictor of conversion from mild cognitive impairment (MCI) to dementia of Alzheimer disease type. However, this association between apathy and dementia conversion has not yet been confirmed in vascular MCI, especially post‐stroke MCI. The aim of this study was to evaluate whether apathy would increase the risk of dementia conversion in patients with post‐stroke MCI after 6 months. Method: A prospective multi‐centre cohort study was performed in 14 clinics in seven provinces and cities of China. A total of 989 subjects were included 2 weeks to 6 months after stroke, and met the diagnostic criteria of International Working Group for MCI. Symptoms of apathy were assessed using the apathy subscale of Geriatric Depression Scale. Subjects were divided into an apathy group ( n = 128) and a non‐apathy group ( n = 861). The primary outcome was the dementia conversion after 6 months. To eliminate potential biases, subjects were chosen from 861 non‐apathy patients with similarity in seven potential predictors of cognitive impairment to match with the apathy group ( n = 128) at a 1:1 ratio, as a matched non‐apathy group ( n = 128). The dementia conversion rate was compared between the apathy group ( n = 128) and its correspondingly matched non‐apathy group ( n = 128), and the relative risk (RR) was calculated. Results: The prevalence of apathy in post‐stroke MCI was 12.9%. After 6 months, 5.2% of patients with post‐stroke MCI converted to dementia. The dementia conversion rate of the apathy group was significantly higher than that of the non‐apathy group before case‐matching (17.2% vs 3.4%, P < 0.001), and also after case‐matching (17.2% vs 6.3%, P < 0.001). Symptoms of apathy increased the risk of conversion from MCI to dementia (RR 2.75, 95% CI 1.272–5.947, P < 0.001). Conclusions: For patients with post‐stroke MCI, apathy symptoms increase the risk of conversion from MCI to dementia.